Pelayanan Prima Perpustakaan dalam Menarik Minat Kunjungan Pengguna (Studi Deskriptif di Perpustakaan UPI Bandung): Studi Deskriptif Kuantitatif di Perpustakaan UPI Bandung - Citra Auliya; Aryanti; Andis Nurrobbani; Ipan Andrian; Nur Azizah; Dyah Bayu Franmesthi (LPPM Politeknik Pajajaran ICB Bandung, 2025)
The purpose of this study is to explore the role of excellent service implementation in fostering users’ interest in visiting the Universitas Pendidikan Indonesia (UPI) Bandung Library. A descriptive quantitative method was applied by distributing questionnaires to 15 UPI students who had experienced library services. Service quality was evaluated based on five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The results reveal that excellent service implementation at the UPI Bandung Library is generally well performed, with empathy emerging as the highest-rated dimension, highlighting the importance of staff friendliness, care, and responsiveness to users’ needs in enhancing satisfaction and visit interest. The assurance dimension also received high ratings, reflecting staff professionalism and clarity of information. However, improvements in physical facilities and service consistency are still needed to support sustainable service quality enhancement.